Wet Noodle Quality Improvement Using Paste Breadfruit (Artocarpus altilis) - Yustina, Ita (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.238, 2017)
Breadfruit is an annual crop fruit that commonly cultivated without fertilize and pesticide application. It has special character whit low water content, high carbohydrates and less sugar, which tend to make it less utilized. Therefore, as a carbohydrate source, breadfruit can be used as material in noodles processing. The research was conducted in the post harvest laboratory, Assessment Institute for Agriculture Technology (AIAT) of East Java. It was using completely randomized design with a factor of breadfruit substitution. The treatment was consisted 10% breadfruit flour, 20% breadfruit flour, 30% breadfruit flour, 20% breadfruit paste, 30% breadfruit paste, 40% breadfruit paste, and a control. The observation parameters consist of: 1) physical properties such as expanded power, water holding capacity, stretching and color; 2) chemical properties including protein content, moisture, and fiber content, 3) organoleptical properties namely color, aroma, taste, and texture. The results showed that noodles with bread substitution of breadfruit paste 20% had the best physical and chemical character that is 150.76% expansion, 1.32% water absorption, 70% tensile strength, brightness level of 59.40, 5.20 protein level %, water content 59,85%, fiber content 3,18%, while according to result of organoleptic quality test best treatment is substitution of breadfruit paste 30% with color score 3,68, taste score 3,80, texture score 3,96, and an overall score of 3.76. Key words: organic food source, breadfruit, noodles, physical properties, chemical properties, organoleptical properties.